The Use of Dexmedetomidine, Midazolam, and Ketamine in Prevention of Emergence Agitation in Pediatric Patients Undergoing Surgery Under General Anesthesia - Syilfana, Hanifah; Indra, Beni; Welan, Rahmani; Effendi, Rinal; Rustam, Erlina (Indonesian Journal of Anesthesiology and Reanimation, 2024)
Introduction: Emergence agitation (EA) is a problem that often occurs in pediatric patients during recovery from anesthesia. The cause of EA remained unclear, but the combination of etiologies increases the risk of postoperative agitation. The researchers use various drugs such as ketamine, midazolam, and dexmedetomidine to prevent and treat EA. Objective: This review aims to determine the effectiveness of dexmedetomidine, midazolam, and ketamine in preventing emergence agitation in pediatric patients undergoing surgery under general anesthesia. Method: This literature review is a narrative review that looks at the outcomes of randomized controlled trials (RCT) studies that tested how well dexmedetomidine, midazolam, and ketamine worked at keeping pediatric patients from becoming agitated during emergence. Literature was collected through Google Scholar and PubMed using the keywords Pediatric, Children, Dexmedetomidine, Ketamine, Midazolam, Emergence Agitation, Emergence Delirium, Postoperative Agitation, and Postoperative Delirium and published within the last ten years (2011–2021) in English or Indonesian. The researchers excluded articles that were not available in full, as well as literature reviews. Results: Based on the specified database and keywords identified, there were 695 articles. This literature study included thirteen articles that met the inclusion criteria. Ten articles examined the effectiveness of dexmedetomidine, four reviewed the effectiveness of midazolam, and three examined the effectiveness of ketamine. Conclusion: According to the ten reviewed articles, administering dexmedetomidine or ketamine reduced the incidence of emergence agitation in children. However, the administration of midazolam yielded inconsistent results. To evaluate the optimal dosage, route, and timing of dexmedetomidine, midazolam, and ketamine in preventing EA, further studies are necessary.